Melancholy, love, and time : boundaries of the self in ancient literature - Toohey, Peter, 1951- (University of Michigan Press, 2004)
"Ancient literature features many powerful narratives of madness, depression, melancholy, lovesickness, simple boredom, and the effects of such psychological states upon individual sufferers. Peter Toohey turns his attention to representations of these emotional states in the classical, Hellenistic, and especially the Roman imperial periods in a study that illuminates the cultural and aesthetic significance of this emotionally charged literature. Toohey also examines some of the ways that the "self" was (or was not) formulated in ancient literature, looking at conditions that could be said to endanger the fragile stability of "self" and how the "self," in ancient experience, was reestablished. Ancient representations of suicide, the perception of time, and the formulation of leisure, Toohey argues, challenge the widespread orthodoxy that melancholic emotions were somehow "discovered" during the European Enlightenment. Blending ancient literature, ancient art, modern psychological theory, and modern literature into his interpretive matrix, Toohey concludes that, paradoxically, difficult emotional registers represent key modes for buttressing an individual's sense of self in both the ancient and modern world. Melancholy, Love, and Time makes an important contribution to classical studies, comparative literature, cultural studies, the history of psychology and medicine, as well as to the burgeoning field of the history of emotions."